Implementasi Program Pinjaman Dana Bergulir Bagi Usaha Mikro Kecil Dan Menengah (UMKM) Di Kabupaten Banyumas - Isna Rahmadani; Simin Simin; Dwiyanto Indiahono (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2020)
Implementation is a process of policy administering that affects the execution, contents, and the impacts. In order to find out whether or not a program is able to reach its goal, there needs to be a study on the policy implementation. A revolving fund loan program is a program that helps small, micro, and medium enterprises in Banyumas Regency in which the loan can be pulled back. The goal of this program is to strengthen the interest aspect for these enterprises to increase the potential of a productive society, the growth of the local economy, to spread out working opportunities that will impact on poverty alleviation in that society. This research focuses on the implementation of the revolving fund loans for the small, micro, and medium enterprises. Method that is used in this research is a qualitative method. This research is done in Banyumas area. The data analysis is done by using an interactive analysis. The result of the implementation shows that this program has not been implemented well. The receivers of this program think that it is a helpful one, especially in helping them grow their business. However, bad credits in this program are still taking place, and there has not been a proper solution up until today. This situation happens because the receivers of the fund are often disobedient in paying their credit. Furthermore, there is no intense supervision after the revolving funds are distributed to those enterprises.